A magnetic topological insulator in two-dimensional EuCd2Bi2: giant gap with robust topology against magnetic transitions. Issue 3 (18th December 2020) - Wang, Hao; Mao, Ning; Hu, Xiangting; Dai, Ying; Huang, Baibiao; Niu, Chengwang
Abstract : We predict that two-dimensional EuCd2 Bi2 is a magnetic topological insulator with a giant nontrivial bandgap and robust against magnetic transitions. Abstract : Magnetic topological states open up exciting opportunities for exploring fundamental topological quantum physics and innovative design of topological spintronics devices. However, the nontrivial topologies, for most known magnetic topological states, are usually associated with and may be heavily deformed by fragile magnetism. Here, using a tight-binding model and first-principles calculations, we demonstrate that a highly robust magnetic topological insulator phase, which remains intact under both ferromagnetic and antiferromagnetic configurations, can emerge in two-dimensional EuCd2 Bi2 quintuple layers. Because of spin–orbital coupling, an inverted gap with intrinsic band inversions occuring simultaneously for up and down spin channels is obtained, accompanied by a nonzero spin Chern number and a pair of gapless edge states, and remarkably the magnitude of the nontrivial band gap for EuCd2 Bi2 reaches as much as 750 meV. Moreover, the robustness of the magnetic TI phase is further confirmed by rotating the magnetization directions, indicating that EuCd2 Bi2 represents a promising material for understanding and utilizing the topological insulating states in two-dimensional spin–orbit magnets.